Ant colony system with heuristic function for the travelling salesman problem - Alobaedy, Mustafa Muwafak; Ku-Mahamud, Ku Ruhana (2013)
Ant colony system which is classified as a meta-heuristic algorithm is considered as one of the best optimization algorithm for solving different type of NP-Hard problem including the travelling salesman problem.A heuristic function in the Ant colony system uses pheromone and distance values to produce heuristic values in solving the travelling salesman problem.However, the heuristic values are not updated in the entire process to reflect the knowledge discovered by ants while moving from city to city. This paper presents the work on enhancing the heuristic function in ant colony system in order to reflect the new information discovered by the ants.Experimental results showed that enhanced algorithm provides better results than classical ant colony system in term of best, average and standard of the best tour length.